Che cosa significa amare l’umanità?: Charles Taylor legge Dostoevskij all’ombra degli anni di piombo - Costa, Paolo (Annali di studi religiosi, 2014)
The essay offers an in-depth analysis of the unpublished manuscript that served as the basis for a series of lectures on Dostoevsky held by Charles Taylor at Berkeley in 1974. In these pages, the Canadian philosopher addresses a problem that has remained central to his reflection also in subsequent decades: the sources of the human capacity to do good in spite of the limits of human nature. By relying on the concept of evil exposed narratively in The Possessed, Taylor shows how a full affirmation of human life must necessarily pass through a relativization of its value, which is made possible, ultimately, by the recognition of the complex dialectical relationship linking good and evil in the human soul.